A cost-effectiveness analysis of demand- and supply-side education interventions: the case of PROGRESA in Mexico - Coady, David; Parker, Susan W. (Wiley, 2004)
The paper is concerned with the issue of the most cost‐effective way of improving access to education for poor households in developing countries. The authors consider two alternatives: extensive expansion of the school system (i.e., bringing education to the poor), and subsidizing investment in education by the poor (i.e., bringing the poor to the education system). To this end, the authors evaluate PROGRESA, a large poverty‐alleviation program recently introduced in Mexico, which subsidizes education. Using double‐difference regression estimators on data collected before and after the program for randomly selected “control” and “treatment” households, the relative impacts of the demand‐ and supply‐side program components are estimated. Combining these estimates with cost information, it is found that the demand‐side subsidies are substantially more cost‐effective than supply‐side expansions.